2019
DOI: 10.1021/acs.jafc.8b06073
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effects and Mechanisms of Ginsenoside Compound K on Myelosuppression

Abstract: Ginsenoside compound K (CK) is not a ginsenoside that naturally exists in Panax ginseng Meyer. However, CK is a major metabolite of ginsenoside Rb1, Rb2, or Rc in the intestine under the effects of bacteria. In this study, we first investigated the effects of CK on myelosuppression in mice induced by cyclophosphamide (CTX). The respective quantities of white blood cells, blood platelets, and bone marrow nucleated cells (BMNCs) were determined to be 8.54 ± 0.91 (109/L), 850.90 ± 44.11 (109/L), and 1.45 ± 0.22 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…CK is the main active product of Rb1, and the regulatory effect of CK on T cells activation has been proved in our previous studies (Chen et al 2014(Chen et al , 2015, so the regulation of T-cells may contribute to the effect of CK in elimination of anaemia. Recently, it has been reported that CK could control apoptosis and promote cells to enter the normal cell cycle through Bcl-2/Bax and MEK/ERK, and exert protective effect on myelosuppression induced by cyclophosphamide in mice (Han et al 2019). Based on these studies, we can speculate that the effect of combination of CK and MTX on anaemia in AA rats may be due to the protective effect of CK on myelosuppression and regulatory effect on T-cells.Steroidal anti- inflammatory drugs can be used in the treatment of RA and anaemia in RA.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…CK is the main active product of Rb1, and the regulatory effect of CK on T cells activation has been proved in our previous studies (Chen et al 2014(Chen et al , 2015, so the regulation of T-cells may contribute to the effect of CK in elimination of anaemia. Recently, it has been reported that CK could control apoptosis and promote cells to enter the normal cell cycle through Bcl-2/Bax and MEK/ERK, and exert protective effect on myelosuppression induced by cyclophosphamide in mice (Han et al 2019). Based on these studies, we can speculate that the effect of combination of CK and MTX on anaemia in AA rats may be due to the protective effect of CK on myelosuppression and regulatory effect on T-cells.Steroidal anti- inflammatory drugs can be used in the treatment of RA and anaemia in RA.…”
Section: Discussionmentioning
confidence: 76%
“…Recently, it has been reported that CK could control apoptosis and promote cells to enter the normal cell cycle through Bcl-2/Bax and MEK/ERK, and exert protective effect on myelosuppression induced by cyclophosphamide in mice (Han et al. 2019 ). Based on these studies, we can speculate that the effect of combination of CK and MTX on anaemia in AA rats may be due to the protective effect of CK on myelosuppression and regulatory effect on T-cells.Steroidal anti-inflammatory drugs can be used in the treatment of RA and anaemia in RA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Post high-dose CTX chemotherapy for clinical cancer treatment always leads to severe pancytopenia, which could result in potential life-threatening infections [22]. White blood cells (WBC), also called leukocytes, are the cells of the immune system that are involved in protecting the body against both infectious disease and foreign invaders.…”
Section: Resultsmentioning
confidence: 99%